Drag estimation on wedge-shaped protuberances in high-speed flows - Kshitij, Abhinav; Prince, Simon A.; Stollery, John L. (American Institute of Aeronautics and Astronautics (AIAA), 2020)
A semi-empirical method is developed to estimate drag on wedge-shaped projections in hypersonic flow. Force balance measurements from gun tunnel tests directly measure total drag on blunt wedges, where the boundary layer and the entropy layer are weakly coupled. Detailed flowfield analysis from numerical simulations provides estimated locations of peak pressure ratio and skin friction. Schlieren images are used for detecting incipient separation in incoming flows with laminar and turbulent boundary layers. Test results indicate the presence of local hotspots at reattachment points of strong detached shocks on the wedge compression ramp, and of primary and secondary vortical structures around lateral faces. Total drag is found to decrease with decreasing bluntness but increasing slenderness in wedges tend to increase skin friction drag.